STRATEGI PENANAMAN SILA KEDUA PANCASILA DALAM PEMBELAJARAN TEMATIK DI KELAS RENDAH SDN 6 SUNGAI KUNYIT - Ruslan, .; Asrori, Muhammad; Totok, Antonius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to obtain a comprehensive information about the strategy of planting the two principles of Pancasila in thematic learning in the low grade of Primary School 6 Sungai Kunyit Mempawah which is related to planning, implementation and evaluation of the second principle of Pancasila. The findings are as follows: Planning of learning to plant the grains of the two principles of Pancasila in learning in the low grade Primary School 6 Sungai Kunyit is a strategy of play and story telling strategy, and not yet contained in the RPP. Implementation of the second principle of Pancasila in the thematic lesson in the low grade of Primary School 6 Sungai Kunyit can be seen from the learning process that has been implemented there are weaknesses in implementing the learning because not maximally apply thematic learning with the material of the second Pancasila, still look not connected with themes. Evaluation of the learning of the second Pancasila sila cultivation in the thematic lesson in the low grade of Primary School 6 Sungai Kunyit is through oral assessment by questioning the students, doing the assessment based on the activity in the class by looking at the activity and the interaction.Keywords: Strategy, planning, the second principle ofÂ  Pancasila, low class